Why have SGLT2 Inhibitors Failed to Achieve the Desired Success in COVID-19? - Cumhur Cure, Medine; Cure, Erkan (Current Pharmaceutical Design, 2024)
The SARS-CoV-2 virus emerged towards the end of 2019 and caused a major worldwide pandemic lasting at least 2 years, causing a disease called COVID-19. SARS-CoV-2 caused a severe infection with direct cellular toxicity, stimulation of cytokine release, increased oxidative stress, disruption of endothelial structure, and thromboinflammation, as well as angiotensin-converting enzyme 2 (ACE2) down-regulation-mediated renin-angiotensin system (RAS) activation. In addition to glucosuria and natriuresis, sodium-glucose transport protein 2 (SGLT2) inhibitors (SGLT2i) cause weight loss, a decrease in glucose levels with an insulin-independent mechanism, an increase in erythropoietin levels and erythropoiesis, an increase in autophagy and lysosomal degradation, Na+/H+-changer inhibition, prevention of ischemia/reperfusion injury, oxidative stress and they have many positive effects such as reducing inflammation and improving vascular function. There was great anticipation for SGLT2i in treating patients with diabetes with COVID-19, but current data suggest they are not very effective. Moreover, there has been great confusion in the literature about the effects of SGLT2i on COVID-19 patients with diabetes . Various factors, including increased SGLT1 activity, lack of angiotensin receptor blocker co-administration, the potential for ketoacidosis, kidney injury, and disruptions in fluid and electrolyte levels, may have hindered SGLT2i's effectiveness against COVID-19. In addition, the duration of use of SGLT2i and their impact on erythropoiesis, blood viscosity, cholesterol levels, and vitamin D levels may also have played a role in their failure to treat the virus. This article aims to uncover the reasons for the confusion in the literature and to unravel why SGLT2i failed to succeed in COVID-19 based on some solid evidence as well as speculative and personal perspectives.
Keywords: angiotensin-converting enzyme 2 (ACE2)